Dampak Ekonomi Fintech dalam Perspektif Maqasid Al-Syariah - Maftukhatusolikhah Maftukhatusolikhah; M. Iqbal; Qodariah Barkah (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
There is a deeply gap in credit distribution that could distributed by the bank escpecially in the covid pandemic era. From Rp1.600 billion credits existing in society is only Rp 600 bankable. The rest (Rp 1.000 billion) is unbankable and has potential FinTech business overdraft. A big question rises to this research is how impact of FinTech in the economic growth’s frame work and how impact of FinTech in the maqasid al-Syariah’s perspectif. Diver from previous research that mainly explored the FinTech from economic and finance perspectives, this research is likely as a basic exploration that explores the FinTech in the sense of economics growth and maqasid al-Syariah. A deeply elaboration on FinTech issues related to economic growth frame works and Maqasid al-Syariah in more systimatic ways. FinTech has a positive impact on 4 (four) component namely, on consument, individual investor, firms, and goverment.